2020
DOI: 10.1038/s41419-020-02852-9
|View full text |Cite
|
Sign up to set email alerts
|

Correction: LEF1 mediates osteoarthritis progression through circRNF121/miR-665/MYD88 axis via NF-кB signaling pathway

Abstract: An amendment to this paper has been published and can be accessed via a link at the top of the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Functional analysis revealed that circRNF121 and MYD88 are involved in the modulation of ECM degradation, apoptosis, and proliferation of chondrocytes. OA progression takes place by promoting ECM degradation through circRNF121/miR-665/MYD88 axis via the NF-кB pathway [74]. Zhang et al explored the role of CircRNA-CDR1as in ECM degradation via sponging miR-641 [75].…”
Section: Osteoarthritis (Oa)mentioning
confidence: 99%
“…Functional analysis revealed that circRNF121 and MYD88 are involved in the modulation of ECM degradation, apoptosis, and proliferation of chondrocytes. OA progression takes place by promoting ECM degradation through circRNF121/miR-665/MYD88 axis via the NF-кB pathway [74]. Zhang et al explored the role of CircRNA-CDR1as in ECM degradation via sponging miR-641 [75].…”
Section: Osteoarthritis (Oa)mentioning
confidence: 99%